A Select Subset of Electron Transport Chain Genes Associated with Optic Atrophy Link Mitochondria to Axon Regeneration in Caenorhabditis elegans - Knowlton, Wendy M.; Hubert, Thomas; Wu, Zilu; Chisholm, Andrew D.; Jin, Yishi (Frontiers in Neuroscience, 2017)
The role of mitochondria within injured neurons is an area of active interest since these organelles are vital for the production of cellular energy in the form of ATP. Using mechanosensory neurons of the nematode Caenorhabditis elegans to test regeneration after neuronal injury in vivo, we surveyed genes related to mitochondrial function for effects on axon regrowth after laser axotomy. Genes involved in mitochondrial transport, calcium uptake, mitophagy, or fission and fusion were largely dispensable for axon regrowth, with the exception of eat-3/Opa1. Surprisingly, many genes encoding components of the electron transport chain were dispensable for regrowth, except for the iron-sulfur proteins gas-1, nduf-2.2, nduf-7, and isp-1, and the putative oxidoreductase rad-8. In these mutants, axonal development was essentially normal and axons responded normally to injury by forming regenerative growth cones, but were impaired in subsequent axon extension. Overexpression of nduf-2.2 or isp-1 was sufficient to enhance regrowth, suggesting that mitochondrial function is rate-limiting in axon regeneration. Moreover, loss of function in isp-1 reduced the enhanced regeneration caused by either a gain-of-function mutation in the calcium channel EGL-19 or overexpression of the MAP kinase DLK-1. While the cellular function of RAD-8 remains unclear, our genetic analyses place rad-8 in the same pathway as other electron transport genes in axon regeneration. Unexpectedly, rad-8 regrowth defects were suppressed by altered function in the ubiquinone biosynthesis gene clk-1. Furthermore, we found that inhibition of the mitochondrial unfolded protein response via deletion of atfs-1 suppressed the defective regrowth in nduf-2.2 mutants. Together, our data indicate that while axon regeneration is not significantly affected by general dysfunction of cellular respiration, it is sensitive to the proper functioning of a select subset of electron transport chain genes, or to the cellular adaptations used by neurons under conditions of injury.